PENGEMBANGAN BUKU AJAR PENDIDIKAN AGAMA ISLAM BERBASIS PENDIDIKAN KARAKTER DAN JIWA NASIONALIS - Isgandi, Yiyin; Prasodjo, Pandu (TARBAWY : Indonesian Journal of Islamic Education, 2018)
The quality of Islamic Religion Education textbooks is still considered to be minimum. It has not been effective yet and been less valuable for pre-teacher students in teacher training and education university. This research aims to develop the PAI textbook based on characters education and nationalist soul in order to reduce radicalization towards religious understanding. Research method used in this research was research and development. The subjects and objects of this paper were PAI textbook and students of STKIP Al-Hikmah Surabaya. The data collected were analyzed both qualitatively and quantitatively. The results show that the book meets the needs of pre-teacher students. The studentsâ€™ responses towards the effectiveness, the quality, the standardization, and the value of developed PAI Textbook products is higher than the old book. The newest handbook average percentage is 85% compared to the old book, which shows 50% in percentage. This book is very valid and worth to use. The results of joint validation according to the expert reviewers and the students indicate that this book is suitable to use and it is categorized as "Very Good" which has 4.32 or 86% percentage in average score.Buku Ajar Pendidikan Agama Islam masih memiliki kualitas standar minimal, belum efektif, dan kurang bernilai tambah bagi calon pendidik di perguruan tinggi keguruan dan ilmu pendidikan. Penelitian ini bertujuan untuk mengembangkan Buku Ajar PAI berbasis pendidikan karakter dan jiwa nasionalis sebagai upaya deradikalisasi pemahaman agama. Metode penelitian menggunakan penelitian dan pengembangan. Subjek dan obyek penelitian adalah Buku Ajar PAI dan mahasiswa STKIP Al-Hikmah Surabaya. Data yang terkumpul dianalisis secara kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa buku ini memenuhi kebutuhan calon pendidik. Nilai rata-rata respon mahasiswa terhadap efektifitas, kualitas, standarisasi, dan nilai tambah produk buku PAI baru lebih tinggi daripada buku lama. Persentase skor rata-rata buku baru 85%, Â lebih tinggi daripada buku lama 50%. Buku ini juga sangat valid dan layak untuk digunakan. Hasil validasi menurut pakar ahli dan mahasiswa menunjukkan buku ini layak digunakan dengan predikat â€œSangat Baikâ€ dengan skor rata-rata 4,32 atau persentase 86%.Â